A novel RRGW derived peptide is a promising inhibitor of BoNT/A. (31st December 2023) - Ma, Wantong; Wang, Lulu; Tan, Xiangmin; Wang, Xin; Yang, Chunyan; Wang, Yu; Liu, Ziye; Liu, Bo; Zhu, Hai; Zhi, Dejuan; Wang, Dongsheng
Abstract: Clostridium botulinum neurotoxin type A (BoNT/A) is one of the most potent biotoxins ever known. Its entry into neurons could block vesicle exocytosis to abolish the release of neurotransmitters from nerve terminals, thus leading to muscle paralysis. Although there are so many peptides, antibodies and chemical compounds claimed to have anti-toxin activity, no drug is available in the clinical application except equine antitoxin serum. In the present work, a short peptide inhibitor RRGW of BoNT/A was firstly identified by computer-aided ligand-receptor binding simulation, then an RRGW derived peptide was rational designed based on the fragment of SNAP-25 (141–206 aa). Proteolytic assay showed that the anti-toxin activity of the RRGW derived peptide was much higher than that of RRGW. Digit abduction score assay demonstrated that the derived peptide delayed BoNT/A-induced muscle paralysis at a lower concentration by 20-fold than RRGW. The results supported that RRGW derived peptide can be a potential BoNT/A inhibitor candidate for further treating botulism. GRAPHICAL ABSTRACT: UF0001